Analisis Pengembangan Video Pembelajaran Fisika Berbasis CTL pada Materi Fluida - Dira Novisya*; Desnita Desnita (Universitas Syiah Kuala, 2020)
Needs analysis becomes an empirical basis for developing research. Data and studies are produced from a complete needs analysis in producing the right product. In this study the analysis was conducted as a preliminary study to reveal the needs of stake holders for CTL-based videos for fluid material. Applied survey research methods with quantitative and qualitative approaches. Research objects related to student characteristics, learning resources, teaching materials and learning media. Quantitative and qualitative data collection procedures use questionnaire and interview instruments. Technical analysis of quantitative dataprocess and categorize data while qualitative data reduces, presents and verifies data. Obtained the results of student characteristics are good, but the aspect of interest shows the lowest value, especially solving and finding solutions to problems of daily life. The media teachers use to teach fluids are powerpoints, images and videos. Learning resources are only textbooks equipped with teaching materials in the form of encyclopedias, modules and worksheets that contain a collection of questions that do not provide experience in solving everyday problems. These findings indicate that the cause of the lack of student interest in solving everyday problems and the low student learning outcomes is that learning media is not in accordance with needs. Media is needed that can facilitate students solving everyday problems. Fluid material that has many daily applications, media needed in the form of CTL-based video. Besides CTL-based videos can display phenomena in full, videos can also develop students' higher-order thinking skills by thoroughly analyzing the phenomena that are displayed